Knee joint dislocation: overview and current concepts. (2nd December 2021) - Anazor, Fitzgerald C; Baryeh, Kwaku; Davies, Neville C
Abstract : Knee joint dislocation is a relatively uncommon injury but its management is important because of the associated high risk of vascular, neurological and multi-ligamentous knee injuries. Clinicians must be aware that not all knee dislocations are diagnosed on plain X-rays; a high index of suspicion is required based on clinical evaluation. Multidisciplinary specialist care is required in all cases to achieve best outcomes. Early one-stage or multiple staged ligament repair and reconstruction offer better outcomes, but most patients have some long-term functional limitation. This article provides insights into the epidemiology and management of this injury and its devastating effects.